2007
DOI: 10.1038/ng2103
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 7 receptor α chain ( IL7R ) shows allelic and functional association with multiple sclerosis

Abstract: Multiple sclerosis is a demyelinating neurodegenerative disease with a strong genetic component. Previous genetic risk studies have failed to identify consistently linked regions or genes outside of the major histocompatibility complex on chromosome 6p. We describe allelic association of a polymorphism in the gene encoding the interleukin 7 receptor alpha chain (IL7R) as a significant risk factor for multiple sclerosis in four independent family-based or case-control data sets (overall P = 2.9 x 10(-7)). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
494
5
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(561 citation statements)
references
References 50 publications
40
494
5
11
Order By: Relevance
“…Several other loci showed some evidence of association, but fell short of strict genome‐wide significance thresholds; these have been subsequently validated in larger studies. The three significant findings were simultaneously replicated in independent studies from the United Kingdom, the United States and the Nordic countries 31, 32. This opened the floodgates, with several successive studies GWAS and meta‐analysis followed in rapid succession, so that by 2011, common variants in 26 genomic loci had been associated with MS risk and independently replicated, but clearly only explained a fraction of MS risk attributable to genetic factors 33, 34, 35, 36, 37, 38, 39, 40, 41, 42.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Several other loci showed some evidence of association, but fell short of strict genome‐wide significance thresholds; these have been subsequently validated in larger studies. The three significant findings were simultaneously replicated in independent studies from the United Kingdom, the United States and the Nordic countries 31, 32. This opened the floodgates, with several successive studies GWAS and meta‐analysis followed in rapid succession, so that by 2011, common variants in 26 genomic loci had been associated with MS risk and independently replicated, but clearly only explained a fraction of MS risk attributable to genetic factors 33, 34, 35, 36, 37, 38, 39, 40, 41, 42.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 72%
“…The development of genetic maps covering much of the genome led to linkage analyses in extended MS affected families from a number of countries, primarily of European ancestry 23, 24, 25, 26, 27, 28, 29, 30, 31, 32. These validated the HLA association but showed no significant linkage to loci outside the MHC.…”
Section: Early Genetic Studiesmentioning
confidence: 99%
“…[1][2][3] Recently, also a detailed genetical analysis found associations with MS risk at different levels in the entire IL-7Ra pathway, for example, in the IL-7 gene itself and in the downstream signaling molecules TYK2 and SOCS1 involved in cytokine signaling and secretion. 4 The IL-7Ra/IL-7 axis is an interesting candidate in autoimmunity, because it is an important survival factor for CD4 and CD8 T cells, and is involved in early B-cell development.…”
Section: Introductionmentioning
confidence: 99%
“…7 Increased expression of the IL-7Ra on T-and B-lymphocytes and macrophages in RA and undifferentiated arthritis compared with osteoarthritis was found in the inflamed joint. 8 A transfection study showed that the MS risk single-nucleotide polymorphism (SNP) rs6897932 [C] caused more exon 6 mRNA splicing, which encodes the transmembrane domain of the receptor, 3 potentially leading to altered soluble levels of the receptor. A recent study correlated rs6897932 [C] with sIL-7Ra on protein level, but could not detect differences between MS patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Polymorphisms of other genes related to the immunological response, namely IL7R and IL2RA, also contribute, albeit more modestly, to the risk of suffering MS (odds ratio (OR) values: 1.18-1.34). [4][5][6][7] In Germans, 8 RR-MS is associated with deficiency of the A3 member of the leukocyte immunoglobulin (Ig)-like receptor family (LILRA3, CD85e), molecule earlier referred to as Ig-like transcript 6 (ILT6), leukocyte Ig-like receptor 4 (LIR-4) or HM43. [9][10][11] The LILRA3 gene maps to the leukocyte receptor complex 12 (LRC,19q13.4), which encodes multiple polymorphic proteins with Ig-like extracellular domains.…”
Section: Introductionmentioning
confidence: 99%